THU0224 THE HEPATITIS VIRUS PRES1 PROTEIN RETARDS THE ONSET OF LUPUS-LIKE GLOMERULONEPHRITIS IN NZB/W F1 MICE. (June 2019) - Luisetto, Roberto; Ghirardello, Anna; Villano, Gianmarco; Scanu, Anna; Gatto, Mariele; Oliveira, Felipe Leite de; Pontisso, Patrizia; Doria, Andrea
Abstract : Background: Infection can trigger autoimmunity but the nature of the pathogen could enhance or inhibit the onset of the disease. In this study we tested the tolerogenic effect of the surface Hepatitis B Virus capside protein preS1 in a lupus mouse model. Objectives: To evaluate the effect of administration of Hepatitis B virus preS1 subunit to NZB/WF1 mice Methods: Mice (10 each group) were injected with a total volume of 200μl of 32.5 μg PreS1 in 200μl PBS (group 1), 200μl PBS (group 2), 3 times at 11 th, 14 th and 17 th weeks of age. Urine samples were collected weekly to evaluate proteinuria by reactive strips. Blood samples were collected before every injection, at 22 th and 28 th weeks, and at death to evaluate levels of anti-C1q and anti-dsDNA by home-made ELISA tests. Tissues were harvested for histological analyses. Proteinuria free and survival rates were analyzed by Kaplan-Meier method using Mantel-Cox test for comparisons. Neurocognitive functions were evaluated with Staircase, Y-Maze and Forced Swim Test. Results: Anti-dsDNA and Anti-C1q levels (OD±SD) were significantly higher in PBS than in preS1 treated mice (Figure 1 ). Mean proteinuria levels (mg/dl±SD) were higher in PBS than in preS1 treated mice. Proteinuria free survival rate ( <300 mg/dl) was lower in group 2 than group 1 (p=0.016; Figure 2 ). Also survival rate was significantly lower in PBS than in preS1 injected mice (p=0.033). Memory deficits (p<0.01) and anxiety-like behavior was pronounced in PBS treated mice. Severe segmental and focal glomerulonephritis in both groups with large proliferation of mesangial and endothelial cells and Russell bodies were found by histological analysis. Mice treated with preS1 had more chronic inflammation in the kidneys and extramedullary hematopoiesis in the spleen and liver. Notably, in salivary glands, severe acute inflammation was observed in group 1 and chronic inflammation in group 2. Conclusion: HBV capsid protein preS1 causes a delay in the onset of lupus-like glomerulonephrits and ameliorates behavioral disorders in NZW/BF1 mice. This peptide seems to induce a tolerizing rather than a pathogenic effect in these autoimmune prone mice models. References: [1] F. McKinneyet al; T-cell exhaustion, co-stimulation and clinical outcome in autoimmunity and infection. Nature523, 612–616 (2015). [2] T-cell exhaustion, co-stimulation and clinical outcome in autoimmunity and infection. Nature523, 612–616 (2015). [3] D. R. Gettset al, Virus infection, antiviral immunity, and autoimmunity. Immunol. Rev. 255, 197–209 (2013) Disclosure of Interests: None declared